PENGENTASAN KEMISKINAN MELALUI AGROINDUSTRI DI PEDESAAN (STUDI DI DUA DESA LERENG MERAPI, KABUPATEN SLEMAN, DIY) - Hastuti, Hastuti (Jurnal Penelitian Humaniora, 2015)
Abstract The survey research aims as know the poverty description, agroindustry variation and agro industry's role in eliminating the poverty in villages. The research population is the household, which has agroindustry activity in the two poor villages in Sleman Regency, Yogyakarta Special Region (DIY). The election of the sample research is undertaken by using purposive sampling method, which take Fifty respondents by random. The research result shows that the agroindustry salak pondoh agroindustry has along and various linkage and it can absorb the more man power has a role in eliminating the poverty by raising the household income. There are two characters of agroindustry in the research area, i.e. and agroindustry's characteristic as a survival strategy and accumulative strategy. Agroindustry activity is admired as an economic activity, which is able to give the better income to the village inhabitant, if the agroindustry is as accumulative strategy as well as in Wonokerto Village. It is different with the area, in which agroindustry activity is as survival strategy that is, in Glagahardjo village. Their agroindustry as the only choice of the income source cannot promise the better income yet. Agroindustry has an important role in the elimination of poverty in the two research villages, especially in village, which has the progressive and various agroindustry. There, it is find the more number of people who has been free from them poverty. Keywords:poverty and agroindustry